O Ensino da matemática nos anos iniciais - Ribeiro, Andressa Nataly [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This research presents an investigation that focuses the teaching of mathematics in the early years. This is a qualitative research of phenomenological approach and involved, through interviews, teachers from the 1st to 5th year of a municipal school. Our intention is to express what is possible to understand about what are the practices adopted by teachers in the initial years to teach mathematics and what influences their choice?, A question that guides the way in research. From the transcription of interviews, we construct the ideographic and nomothetic analysis. More than phases of analysis, they are movements that allow one to expose individual comprehension, relative to each teacher's say, and general, with convergences of sense and meaning to say what in this group of teachers is understood. With this movement of analysis, we have seen that, although teachers make use of manipulative materials in their classes and emphasize the importance of changing the way they teach mathematics, they are faced with obstacles to the teaching of this discipline: teaching and not just auxiliary material? These obstacles show that, despite the quest that many profess to undertake, their initial training is not enough for them to know the mathematics they will teach

Esta pesquisa apresenta uma investigação que foca o ensino da matemática nos anos iniciais. Desenvolvida em uma abordagem qualitativa de caráter fenomenológico envolveu, por meio de entrevistas, professoras do 1º ao 5º ano de uma escola municipal. Nossa intenção é expressar o compreendido acerca de quais são as práticas adotadas pelos professores nos anos iniciais para ensinar matemática e o que influencia sua escolha?, pergunta que orienta o caminhar na pesquisa. A partir da transcrição das entrevistas, construímos a análise ideográfica e nomotética. Mais do que fases da análise, são movimentos nos quais se procura expor as compreensões em nível individual - relativas ao dizer de cada um dos professores, e de caráter geral, fazendo convergências de sentido e significado para expor o que, nesse grupo de professores, pôde ser compreendido. No movimento de compreensão vimos que, embora os professores façam uso de materiais manipuláveis em suas aulas e destaquem a importância de mudar a maneira de ensinar matemática, eles se deparam com obstáculos ao ensino de matemática do tipo: como usar determinado recurso para ensinar e não apenas como material auxiliar? Vê-se que, apesar da busca que muitos declaram, a formação inicial desses professores não é suficiente para eles conhecerem a matemática que irão ensinar
The Teaching of Mathematics in the Early Years
Keywords: Matemática - Estudo e ensino; Professores - Formação; Fenomenologia; Mathematics Study and teaching